IMPLEMENTASI PENILAIAN PORTOFOLIO PADA PEMBELAJARAN MATEMATIKA POKOK BAHASAN KESEBANGUNAN DAN KEKONGRUENAN KELAS IX SMP MUHAMMADIYAH 1 KARTASURA TAHUN AJARAN 2015/2016 - Widyayati, Yanti (2015)
The purpose of this study was to describe the application assessment portfolio on the material similarity and congruence class IX in SMP Muhammadiyah 1 Kartasura. This qualitative descriptive study took place in SMP Muhammadiyah 1 Kartasura the academic year 2015/2016, against 30 students of class IX C. Data collection technique using observation, interview, test, evaluation and documentation. Based on the data obtained, when using the conventional measure of student report cards score an average of 71.8 while using portfolio assessment average value congruence tests on the material and the material = 81.8 similarity 90. These results indicate 1) the application portfolio assessment in mathematics increased achievement and lasted better over time. 2) The students' response to portfolio assessment in mathematics is very positive. Assessment of the portfolio on a daily observation of students' attitudes and behavior is very good.